Уход за растениями - Петренко С. И. (Энциклопедия комнатного цветоводства, 2006)
Экземпляры: ф.23 (2007) / Инвентарный номер: 51561 / Цена: / Сис.шифр: 42.374 / Авт.знак: П 30 / ГРНТИ: 68.35.57 / ББК: 42.374я2